Physiotherapy outweighed multiple therapy methods of bell’s palsy: A review study (Annals of Medical Research, 2021)
None
Keywords: Bell’s Palsy; Acupuncture; Steroid; Antiviral; İdiopatic; Chiropractic; Proprioceptif; Facilitation.